Gender Differences in Marital Satisfaction: A Meta‐analysis. Issue 1 (February 2014) - Jackson, Jeffrey B.; Miller, Richard B.; Oka, Megan; Henry, Ryan G.
<x xml:space="preserve">Abstract</x> The purpose of the present meta‐analysis was to empirically test the widely held assumption that women experience lower marital satisfaction than men. A total of 226 independent samples with a combined sum of 101, 110 participants were included in the meta‐analysis. Overall results indicated statistically significant yet very small gender differences in marital satisfaction between wives and husbands, with wives slightly less satisfied than husbands; moderator analyses, however, indicated that this difference was due to the inclusion of clinical samples, with wives in marital therapy 51% less likely to be satisfied with their marital relationship than their husbands. The effect size for nonclinical community‐based samples indicated no significant gender differences among couples in the general population. Additional moderator analyses indicated that there were also no gender differences when the levels of marital satisfaction of husbands and wives in the same relationship (i.e., dyadic data) were compared.